2018
DOI: 10.1007/s10072-018-3430-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mechanistic insights of Cas scaffolding protein family member 4 with protein tyrosine kinase 2 in Alzheimer’s disease by evaluating protein interactions through molecular docking and dynamic simulations

Abstract: Cas scaffolding protein family member 4 and protein tyrosine kinase 2 are signaling proteins, which are involved in neuritic plaques burden, neurofibrillary tangles, and disruption of synaptic connections in Alzheimer's disease. In the current study, a computational approach was employed to explore the active binding sites of Cas scaffolding protein family member 4 and protein tyrosine kinase 2 proteins and their significant role in the activation of downstream signaling pathways. Sequential and structural ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…It is notable that the most enriched terms include the regulation of neuron projection development, vesicle localization, establishment of vesicle localization, cotranslational protein targeting to membrane, and protein targeting to endoplasmic reticulum (ER). These results indicated that the alteration of neurofunction [29], protein localization [30], and ER signal transduction [30] possibly participates in the development of AD. The enriched terms related to neurofunction are consistent with the feature of AD as a neurodegenerative disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that the most enriched terms include the regulation of neuron projection development, vesicle localization, establishment of vesicle localization, cotranslational protein targeting to membrane, and protein targeting to endoplasmic reticulum (ER). These results indicated that the alteration of neurofunction [29], protein localization [30], and ER signal transduction [30] possibly participates in the development of AD. The enriched terms related to neurofunction are consistent with the feature of AD as a neurodegenerative disease.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking is a computational approach used to predict the binding conformational behavior of biomolecules, i.e., drugs and proteins. All of the screened drugs were docked and analyzed based on binding affinity (kcal/mol) (see the Supplementary Data S2). From docking results, it has been observed that from 100 FDA-approved drugs, 24 drugs showed binding affinity values higher than −7 kcal/mol and may have good binding potential inside the binding pocket of the EWS protein.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Protein interactions initiate the downstream signaling pathways and are involved in the occurance of neurological diseases 57 , 58 . The decreased flexibility of protein backbone is considered a major hallmark for checking the stability of docked complexes using MD simulation 56 .…”
Section: Conclusion and Discussionmentioning
confidence: 99%